Dental Examination at Day Care Centers for the Elderly - Fujita, Masuhisa; Komemushi, Kazuko; Kihara, Hidefumi; Yamada, Takashi; Yoshida, Yutaka; Fujimoto, Yoshiharu (Ronen Shika Igaku, 1997)
As a means of promoting the dental health of the elderly, the Osaka Higashiyodogowa Ward Dental Association has been conducting dental examination and monitoring the oral health of the elderly. A survey was conducted from October to November in 1996 to determine the general physical and oral health status of the elderly, who utilize the day care services at 6 homes for the elderly located in Higashiyodogawa Ward. A total of 124 subjects, 45 male (36.3 %) and 79 female (63.7%) were examined. The mean age was 75.75±8.19 years, and about 60.5% were observed to have the following conditions; diabetes mellitus (19.4%), cerebrovascular diseases (15.3%), cardiac diseases (13.7%), and hypertension (12.1%). The percentage of subjects who has previously received instruction in proper tooth brushing techniques was 21.3%. Twelve subjects (12.9%) considered dental treatment to be “frightening/painful”, and 17 (13.7%) received regular dental care at dental clinics. The status of oral health was not satisfactory, with soft tissue disease observed in 32 (25.8%), dental plaque in 74 (59.7%), and dental calculus in 71 (57.3%). The mean number of teeth per subject was 10.5±3.2, and although a difference was observed by age group, no sex difference was observed. Dental caries were observed in 47.6% of subjects, and the relation of the dental caries rate to total number of remaining teeth was 18.7%. This was lower than the rate observed in a survey conducted in 1993 on the bedridden elderly. Twenty-nine subjects (23.4%) were edentulous, and 80 (64.5%) has dentures of whom 16 (20.4%) were observed to have improper fit. As a result, it was recognized that prosthetic treatment for missing teeth, treatment for periodontal disease, and improvement in oral cleaning were required in 45.2%, 48.4%, and 66.9% of subjects, respectively. These results will be utilized to achieve an improvement in the quality of life and to promote the dental health of the elderly.